2020
DOI: 10.1111/1365-2664.13683
|View full text |Cite
|
Sign up to set email alerts
|

Greening of grey infrastructure should not be used as a Trojan horse to facilitate coastal development

Abstract: Climate change and coastal urbanization are driving the replacement of natural habitats with artificial structures and reclaimed land globally. These novel habitats are often poor surrogates for natural habitats. The application of integrated greening of grey infrastructure (IGGI) to artificial shorelines demonstrates how multifunctional structures can provide biodiversity benefits whilst simultaneously serving their primary engineering function. IGGI is being embraced globally, despite many knowledge gaps and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 33 publications
1
64
0
Order By: Relevance
“…Ecoengineering complexity and missing microhabitats on these artificial structures to enhance the biodiversity and ecosystem functioning of their communities, is increasingly common. However, scientific studies providing the evidence base for this rapidly growing field are often poorly replicated and carried out over small spatial and temporal scales (Chapman et al, 2018;Firth et al, 2020). Global integration of small-scale ecological experiments such as those conducted here can be useful in identifying appropriate eco-engineering approaches before they are scaled up.…”
Section: Discussionmentioning
confidence: 99%
“…Ecoengineering complexity and missing microhabitats on these artificial structures to enhance the biodiversity and ecosystem functioning of their communities, is increasingly common. However, scientific studies providing the evidence base for this rapidly growing field are often poorly replicated and carried out over small spatial and temporal scales (Chapman et al, 2018;Firth et al, 2020). Global integration of small-scale ecological experiments such as those conducted here can be useful in identifying appropriate eco-engineering approaches before they are scaled up.…”
Section: Discussionmentioning
confidence: 99%
“…With contrasting effects of pH on different taxa (Guilbeau et al 2003), regions with different benthic community assemblages could also be influenced to varying degrees. One of the major criticisms of ecological engineering is that examples are often limited in their scope, and a recent review by Firth et al (2020) suggested revisiting, repeating, and expanding on experiments to test responses over broader spatio-temporal scales to improve the evidence base (Evans et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The attractiveness of NbS comes from their potential to protect society from climate change impacts while slowing further warming, supporting biodiversity, and securing ecosystem services. Yet, many NbS have not rigorously been assessed in terms of reliability, cost‐effectiveness, and resilience to climate change (Lane, 2017; Firth et al ., 2020). It is important to understand the value and limitations of NbS for proper use (e.g.…”
Section: Biogeomorphological Research and Nature‐based Solutionsmentioning
confidence: 99%
“…It is important to understand the value and limitations of NbS for proper use (e.g. Firth et al ., 2020; Seddon et al ., 2020).…”
Section: Biogeomorphological Research and Nature‐based Solutionsmentioning
confidence: 99%
See 1 more Smart Citation